Suisun Marsh : Ecological History and Possible Futures - Jackson, William Franklin; Fiedler, Peggy Lee; Manfree, Amber D.; Moyle, Peter B. (Book collections on Project MUSE., 2014)
"One of California's most remarkable wetlands, Suisun Marsh is the largest tidal marsh on the West Coast and a major feature of the San Francisco Estuary. This productive and unique habitat supports endemic species, is a nursery for native fishes, and is a vital link for migratory waterfowl. The Marsh has been influenced by humans for its entire 6000-year history and human actions will have significant impacts as sea level rises and cultural values shift in the century ahead. This study includes in-depth information about the ecological and human history of Suisun Marsh, its abiotic and biotic characteristics, agents of ecological change, and alternative futures facing this ecosystem"--